Physical activity attenuates the genetic predisposition to obesity in 20,000 men and women from EPIC-Norfolk prospective population study. - Shengxu Li (Public Library of Science (PLoS), 2010)
Background We have previously shown that multiple genetic loci identified by genome-wide association studies (GWAS) increase the susceptibility to obesity in a cumulative manner. It is, however, not known whether and to what extent this genetic susceptibility may be attenuated by a physically active lifestyle. We aimed to assess the influence of a physically active lifestyle on the genetic predisposition to obesity in a large population-based study. Methods and findings We genotyped 12 SNPs in obesity-susceptibility loci in a population-based sample of 20,430 individuals (aged 39-79 y) from the European Prospective Investigation of Cancer (EPIC)-Norfolk cohort with an average follow-up period of 3.6 y. A genetic predisposition score was calculated for each individual by adding the body mass index (BMI)-increasing alleles across the 12 SNPs. Physical activity was assessed using a self-administered questionnaire. Linear and logistic regression models were used to examine main effects of the genetic predisposition score and its interaction with physical activity on BMI/obesity risk and BMI change over time, assuming an additive effect for each additional BMI-increasing allele carried. Each additional BMI-increasing allele was associated with 0.154 (standard error [SE] 0.012) kg/m(2) (p = 6.73 x 10(-37)) increase in BMI (equivalent to 445 g in body weight for a person 1.70 m tall). This association was significantly (p(interaction) = 0.005) more pronounced in inactive people (0.205 [SE 0.024] kg/m(2) [p = 3.62 x 10(-18); 592 g in weight]) than in active people (0.131 [SE 0.014] kg/m(2) [p = 7.97 x 10(-21); 379 g in weight]). Similarly, each additional BMI-increasing allele increased the risk of obesity 1.116-fold (95% confidence interval [CI] 1.093-1.139, p = 3.37 x 10(-26)) in the whole population, but significantly (p(interaction) = 0.015) more in inactive individuals (odds ratio [OR] = 1.158 [95% CI 1.118-1.199; p = 1.93 x 10(-16)]) than in active individuals (OR = 1.095 (95% CI 1.068-1.123; p = 1.15 x 10(-12)]). Consistent with the cross-sectional observations, physical activity modified the association between the genetic predisposition score and change in BMI during follow-up (p(interaction) = 0.028). Conclusions Our study shows that living a physically active lifestyle is associated with a 40% reduction in the genetic predisposition to common obesity, as estimated by the number of risk alleles carried for any of the 12 recently GWAS-identified loci. Please see later in the article for the Editors' Summary.